The Association of Meal Practices and other Dietary Correlates with Dietary Intake among High School Students in the United States, 2010. Issue 6 (July 2015) - Demissie, Zewditu; Eaton, Danice K.; Lowry, Richard; Kim, Sonia A.; Park, Sohyun; Grimm, Kirsten A.; Merlo, Caitlin; Harris, Diane M.
Purpose: To examine behavioral and environmental factors that may be related to dietary behaviors among U.S. high school students. Design: Data were obtained from the 2010 National Youth Physical Activity and Nutrition Study, a cross-sectional study. Setting: The study was school-based. Subjects: Study subjects were a nationally representative sample of students in grades 9 to 12 (n = 11, 458). Measures: Variables of interest included meal practices, in-home snack availability, and intakes of healthful foods/beverages (fruits, vegetables, water, and milk) and less healthful foods/beverages (fried potatoes, pizza, and sugar-sweetened beverages). Analysis: Sex-stratified logistic regression models were used to examine associations of meal practices and snack availability with dietary intake. Odds ratios (ORs) were adjusted for race/ethnicity and grade. Results: Eating breakfast daily, frequent family dinners, and bringing lunch from home were associated with higher odds of consuming at least three healthful foods or beverages. High fast-food intake was associated with lower odds of healthful dietary intake and higher odds of sugar-sweetened beverage intake (female OR = 3.73, male OR = 4.60). Students who mostly/always had fruits and vegetables available at home had increased odds of fruits (female OR = 3.04, male OR = 2.24), vegetables (female OR = 2.12, male OR = 1.65), water (female OR = 1.82, male OR = 1.85), and milk intake (female OR = 1.45, male OR = 1.64). Conclusion: Encouraging daily breakfast consumption, frequent family dinners, and fruit and vegetable availability at home may lead to higher intakes of healthful foods among high school students.